Margin-to-Margin Seafloor Spreading in the Eastern Gulf of Aden: A 16 Ma-Long History of Deformation and Magmatism from Seismic Reflection, Gravity and Magnetic Data - Gillard, Morgane; Leroy, Sylvie; Cannat, Mathilde; Sloan, Heather (Frontiers in Earth Science, 2021)
In this paper we present and analyze spreading-parallel seismic transects that image the oceanic crust in the eastern Gulf of Aden, from the Oman to the Socotra margins, across the active Sheba mid-oceanic ridge and between the Socotra-Hadbeen and Eastern Gulf of Aden Fracture Zones. The correlation of potential field data sets and gravity modelling allow us to document the spreading history of this oceanic basin from the onset of seafloor spreading ~16 Ma-ago to the present. Two main oceanic sub-domains display distinct structural characteristics associated with different magmatic budgets at this mid-ocean ridge. In addition, we document the occurrence of a magmatic pulse at the Sheba Ridge around 11 Ma leading to the construction of a magmatic plateau in the western part of the studied area. This event led to substantial deformation and additional magmatism in previously formed oceanic crust. It could be related to an off-axis magmatic event previously identified in the adjacent Sheba segment, itself possibly related to the Afar plume.